Cloud-based Data Center Design as a Data Storage Infrastructure on Internet of Things - Primananda, Rakhmadhany; Siregar, Reza Andria; Atha, Mochamad (Faculty of Computer Science (FILKOM) Brawijaya University, 2019)
The widespread use of Internet of Things (IoT) has effect in a growing number of hardware devices that can be controlled and monitored using a variety of applications. It affects the amount of data that must be collected to be analyzed and processed according to user requirement. The greater the data collected results in requirement of storage media that has access management and scalability that are effective and efficient. The data collected in cloud-based infrastructure namely Openstack. Implementation in this research by involving two physical device of server as main infrastructure that located in network of Faculty of Computer Science, Brawijaya University Malang which used as controller node and compute node. Controller can adapt to the use of various dashboard and provide a good access management service for users to request and create instances in Openstack. The resulting data center shows good performance based on scalability, access, and performance of data transmission from IoT sensors. The test is done gradually by adding requirement of compute nodes up to 24 VCPU, 48 GB of RAM, and 235 GB of HD storage in registered instances. Access at the data center can be done either from faculty internal network (private) and faculty external network (public) with access time under 100 ms.